European Association of Urology Guidelines on Upper Urinary Tract Urothelial Carcinoma: 2020 Update - Rouprêt, Morgan; Babjuk, Marko; Burger, Maximilian; Capoun, Otakar; Cohen, Daniel; Compérat, Eva M.; Cowan, Nigel C.; Dominguez-Escrig, Jose L.; Gontero, Paolo; Hugh Mostafid, A.; Palou, Joan; Peyronnet, Benoit; et al. (European urology, 2021)
The European Association of Urology (EAU) Guidelines Panel on Upper Urinary Tract Urothelial Carcinoma (UTUC) has prepared updated guidelines to aid clinicians in the current evidence-based management of UTUC and to incorporate recommendations into clinical practice. To provide an overview of the EAU guidelines on UTUC as an aid to clinicians. The recommendations provided in the current guidelines are based on a thorough review of available UTUC guidelines and articles identified following a systematic search of Medline. Data on urothelial malignancies and UTUC were searched using the following keywords: urinary tract cancer, urothelial carcinomas, upper urinary tract carcinoma, renal pelvis, ureter, bladder cancer, chemotherapy, ureteroscopy, nephroureterectomy, neoplasm, adjuvant treatment, instillation, recurrence, risk factors, and survival. References were weighted by a panel of experts. Owing to the rarity of UTUC, there are insufficient data to provide strong recommendations. The 2017 tumour, node, metastasis (TNM) classification is recommended. Recommendations are given for diagnosis and risk stratification as well as for radical and conservative treatment, and prognostic factors are discussed. A single postoperative dose of intravesical mitomycin after nephroureterectomy reduces the risk of bladder tumour recurrence. Kidney-sparing management should be offered as a primary treatment option to patients with low-risk tumour and two functional kidneys. After radical nephroureterectomy, cisplatin-based chemotherapy is indicated in locally advanced UTUC. These guidelines contain information on the management of individual patients according to a current standardised approach. Urologists should take into account the specific clinical characteristics of each patient when determining the optimal treatment regimen, based on the proposed risk stratification of these tumours. Urothelial carcinoma of the upper urinary tract is rare, but because 60% of these tumours are invasive at diagnosis, an appropriate diagnosis is most important. A number of known risk factors exist. Based on the most recent evidence, the 2020 European Association of Urology guidelines on upper urinary tract urothelial carcinoma aim to provide information on the management of individual patients according to a current standardised approach. Urologists should take the specific clinical characteristics of each patient into account when determining the optimal treatment regimen, based on the proposed risk stratification of these tumours.